Resilient resettlement model: Progress and new insights into humanitarian-development Nexus - Norazam Ab Samah; Khamarrul Azahari Razak; Abdullah Mahmud; Dzulkarnaen Ismail; Muhammad Fauzie Ismail; Liyana Hayatun Syamila Ramlee; Bondan Galih Dewanto (Progress in Disaster Science)
An integrated post-disaster recovery (PDR) strategy is pivotal to enhance societal resilience and accelerate our commitment to the Sendai Framework for Disaster Risk Reduction 2015–2030. This study presents the Resilient Resettlement Model (RRM), a novel framework designed to co-implement resilient resettlement solutions in complex disaster contexts. This study aims: i) to identify design considerations derived from empirical observations of past resettlement projects, emphasizing principles: ‘Build Back Better,’ ‘Bounce Back Faster,’ and ‘Strengthen Risk Reduction’; ii) to develop a theoretical framework for resilient resettlement design in post-disaster scenarios; and iii) to establish the RRM to support the Humanitarian-Development Nexus (HDN). Based on the systematic literature reviews, field observations, surveys, evidence-based case studies, and expert validation, this study adopts a two-phase sequential mixed-method design approach based on three significant disasters in the Southeast Asia region. The MERCY Malaysia's involvement in the 2004 Indian Ocean Earthquake and Tsunami in Aceh, Indonesia, the 2014 Kelantan flood in Malaysia, and the 2018 Palu Earthquake and Tsunami in Indonesia were explored to uncover new insights into resettlement implementation model and best practices. The study highlights the critical role of planning and design considerations in successful resettlement efforts. Integrating two decades of international humanitarian experience, this research offers prospective views to the disaster recovery preparedness strategies and recommendations that incorporate physical, environmental, social, economic, and institutional components of design considerations towards achieving resilient post-disaster resettlements.